2016
DOI: 10.1126/sciimmunol.aai7793
|View full text |Cite
|
Sign up to set email alerts
|

Partial exhaustion of CD8 T cells and clinical response to teplizumab in new-onset type 1 diabetes

Abstract: Biologic treatment of T1D typically results in transient stabilization of C-peptide levels (a surrogate for endogenous insulin secretion) in some patients, followed by progression at the same rate as in untreated control groups. Here, we used integrated systems biology and flow cytometry approaches with clinical trial blood samples to elucidate pathways associated with C-peptide stabilization in T1D subjects treated with the anti-CD3 monoclonal antibody teplizumab. We identified a population of CD8 T cells tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
194
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 192 publications
(217 citation statements)
references
References 59 publications
(103 reference statements)
16
194
3
4
Order By: Relevance
“…Similar findings in type I diabetic patients treated with the anti-CD3 monoclonal antibody teplizumab demonstrate the relevance of these new insights into peripheral CD8 tolerance [64]. A population of hypoproliferative EOMES+TIGIT+KLRG1+ CD8+ T cells is readily identified in the blood of patients with the greatest response to anti-CD3 treatment [64]. …”
Section: Ii) Tolerance Mechanisms Associated With Transient Mixed Chimentioning
confidence: 70%
See 1 more Smart Citation
“…Similar findings in type I diabetic patients treated with the anti-CD3 monoclonal antibody teplizumab demonstrate the relevance of these new insights into peripheral CD8 tolerance [64]. A population of hypoproliferative EOMES+TIGIT+KLRG1+ CD8+ T cells is readily identified in the blood of patients with the greatest response to anti-CD3 treatment [64]. …”
Section: Ii) Tolerance Mechanisms Associated With Transient Mixed Chimentioning
confidence: 70%
“…Furthermore, downregulated expression of hypoxia-inducible factor HIFα in tolerant CD8+ T cells [62] is aligned with the low metabolic requirement and the high expression of VHL in exhausted T cells [63]. Similar findings in type I diabetic patients treated with the anti-CD3 monoclonal antibody teplizumab demonstrate the relevance of these new insights into peripheral CD8 tolerance [64]. A population of hypoproliferative EOMES+TIGIT+KLRG1+ CD8+ T cells is readily identified in the blood of patients with the greatest response to anti-CD3 treatment [64].…”
Section: Ii) Tolerance Mechanisms Associated With Transient Mixed Chimentioning
confidence: 91%
“…Bulk RNA-seq libraries were sequenced to target depths of ~10 million reads. RNA-seq pipeline analysis methods have previously been described (25). Quality metrics for aligned reads were obtained using the Picard (v.1.56) suite of tools (https://broadinstitute.github.io/picard/).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of action of teplizumab was initially thought to deplete T cells similar to other immunotherapies that target T cells, such as OKT3, thymoglobulin, and Campath (anti-CD52) [6]. More recently, we reported an increase in the frequency of circulating central memory CD8 T cells in clinical responders [7], and further investigation revealed that accumulation of partially exhausted CD8 T cells, characterized by co-expression of TIGIT and KLRG1 together with high levels of EOMES-associated gene networks, was associated with successful response to teplizumab therapy [8]. These studies suggested that teplizumab therapy, rather than acting as a depleting or blocking antibody, may have agonist properties that lead to changes in the composition of differentiation and activation status within the circulating pool of CD3-expressing T cells.…”
Section: Introductionmentioning
confidence: 99%